Estimating household exposure to pyrethroids and the relative contribution of inhalation pathway in a sample of Japanese children - Yoshida, Toshiaki; Mimura, Mayumi; Sakon, Naomi (Environmental science and pollution research international, 2021)
Several synthetic pyrethroids are suspected to have carcinogenicity or reproductive toxicity. However, there is little knowledge about indoor air pollution in residences or the extent of intake by the residents of the newly developed pyrethroids, transfluthrin, profluthrin, and metofluthrin, although they have been widely used indoors as mosquito repellents and mothproof repellents in recent years. In the present study, the household exposure to pyrethroids through all exposure pathways and the contribution of inhalation pathway in Japanese children were examined by measuring urinary pyrethroid metabolites in the children and the airborne pyrethroids in their residences. Urine excreted first after waking up was collected from subjects aged 6 to 15 years ( n = 132), and airborne pyrethroids were sampled in the subjects’ bedrooms for 24 h. Nineteen pyrethroids and their nine urinary metabolites were measured. Their daily intakes estimated were as follows (median, ng/kg b.w./d): bifenthrin, 56; transfluthrin, 22; metofluthrin, 11; profluthrin, 0.86. The contribution rates of the amounts absorbed by inhalation to the amounts absorbed via all of the exposure pathways while at home tended to decrease in the following order: profluthrin (median 15%) ≈ transfluthrin (14%) > metofluthrin (1%) > bifenthrin (0.1%). Transfluthrin was considered to be the most notable pyrethroid as an indoor air pollutant. Our study demonstrated widespread exposure to transfluthrin, metofluthrin, profluthrin, and bifenthrin in a sample of Japanese children.